College activity attendance registration & scrutinization system using barcode scanner (COLLAARS) / Muhammad Nabil Fikri Jamaluddin ... [et al.] - Jamaluddin, Muhammad Nabil Fikri; Jamil, Mohd Hairul Nazreen; Mohd Fauzi, Shukor Sanim; JM. Gining, Ray Adderley; Hashim, Nur Dini (Universiti Teknologi MARA, Kedah, 2019)
Students’ attendance in all academic institutions is very important and cannot be overlooked because all institutions have certain criteria for their student’s attendance in class, college activities, and examinations. Hence, the lecturers in most academic institutions are concerned with the students’ inconsistent attendance. The manual method of taking attendance is not effective because there are several challenges to that kind of method. The data collected through the conventional method is difficult to manage; time consuming to be scrutinized; and it causes the wastage of human and material resources. Therefore, the aim of this project is to develop a web-based application for handling college activity attendance registration and scrutinization system for college application by using barcode scanner. The special criteria is the web-based application will use the barcode scanner to scan the barcode on students’ matric card in order to retrieve the data. By using the barcode scanner, it can help management to reduce the waste of sources and also help to reduce the need for manual labor to do manual sequential examination for each of student’s data. In short, this project is conducted to find the feasible solution for the related issues by implementing the web-based and barcode technology for the research and development purpose. Also, the prototype enables the management to facilitate in handling the college application and can keep on track the attendance of student’s activity from time to time.